Differences in autonomic neural activity during exercise between the second and third trimesters of pregnancy. Issue 8 (28th April 2016) - Nakagaki, Akemi; Inami, Takayuki; Minoura, Tetsuji; Baba, Reizo; Iwase, Satoshi; Sato, Motohiko
Abstract: Aim: To test the hypothesis that autonomic neural activity in pregnant women during exercise varies according to gestational age. Methods: This cross‐sectional study involved 20 healthy women in their second ( n = 13) or third ( n = 7) trimester of pregnancy. Incremental cardiopulmonary exercise testing was performed with an electromagnetic cycle ergometer. Heart rate variability was analyzed by frequency analysis software. Results: The low‐frequency to high‐frequency (LF/HF) ratio, an indicator of the sympathetic nervous system, was significantly higher in third trimester than in second trimester subjects ( P < 0.05) at 1, 2, and 3 min of incremental exercise testing. In contrast, the HF/total power ratio, an indicator of rapidly acting parasympathetic activity, was significantly higher in second trimester than in third trimester subjects ( P < 0.05) at 2 and 3 min. In addition, a negative correlation was found between gestational age and the 'accumulation half‐time' of the LH/HF ratio, the time point at which the sum of the LF/HF ratio reached 50% of that accumulated in the total 6 min of exercise testing ( r = −0.49, P = 0.028). Conclusions: The autonomic response to exercise in pregnant women differs between the second and third trimesters. These differences should be considered when prescribing exercise to pregnant women.